Mechanistic Modeling of the Thermal Cracking of Decylbenzene. Application to the Prediction of Its Thermal Stability at Geological Temperatures - Burklé-Vitzthum, Valérie; Michels, Raymond; Scacchi, Gérard; Marquaire, Paul-Marie (Industrial & engineering chemistry research, 2003)
Thermal cracking of decylbenzene is experimentally studied at 330 °C under 70 MPa for 10 h to 1 month, that is, up to 20% of conversion. A detailed kinetic model consisting of 946 free-radical reactions and 1 molecular reaction is developed to describe the results. The formation of main products, namely, toluene, ethylbenzene, nonene, nonane, and octane, is correctly described by the model. The global activation energy is equal to 66 kcal·mol-1. The molecular reaction, that is, the retroen reaction, is of great importance: it explains the major part of toluene and nonene formation at 330 °C. At 400 °C this reaction becomes negligible but at 200 °C it is predominant. Its activation energy is about 54 kcal·mol-1 and is confirmed by experimental measurements. The mechanistic kinetic model is applied to the prediction of the thermal stability of decylbenzene at temperatures usually encountered in petroleum sedimentary basins (T < 250 °C). At such temperatures, the main reactive pathway, controlled by the retroen reaction, leads to the formation of toluene. Such conclusion is not intuitive in the geochemistry field and suggests that long-chain alkylbenzenes may inhibit rather than accelerate the cracking of alkanes in natural hydrocarbon mixtures.